Study of adverse drug reactions in out-patient departments of a teaching hospital - Zinnat Ara Begum; Sayeeda Sultana; Badar Uddin Umar; A. H. Ferdous; Md. Kamal Uddin; S. M. Hasibul Islam (Bangladesh Pharmacological Society, 2012)
The study conducted in the Medicine and Skin outpatient departments of Dhaka Medical College, Dhaka revealed 19 cases (7 males, 12 females) of adverse drug reactions (ADR) out of 160 patients. 31.58% ADRs were of mild type, 42.1% were of moderate and 26.32% were of severe in nature. Gastrointestinal complications were the most frequent adverse effect (56%). Antimicrobial drugs were the most common cause of ADR (42.86%) followed by NSAIDs (33.33%). This study is a preliminary study for getting information on the pattern of ADRs in Bangladesh needing further studies.